PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH BANK PENGGUNA E-BANKING DI SURABAYA - Ainul Yaqin; Aniek Maschudah Ilfitriah (Journal of Business & Banking, 2014)
In the global era, the banks created a system of e-banking that is a form of service providedby them for providing customers ease in conducting transactions anytime and anywhere viaonline. However, with e-banking, it is still perceived by customer complaints, such as securityproblems. In addition, the use of e-banking cannot be used by all customers because ofcertain constraints. The aim of this study was to determine the effect of a positive significantrelationship between service qualities on customer loyalty Bank user satisfaction of ebankingin Surabaya. This research method uses questionnaire for collecting the data. Theresearch was conducted in Surabaya, while the analysis was done by using Structural EquationModeling (SEM) with the number of respondents of 115. The results show that the effectof service quality on customer satisfaction and the effect of customer satisfaction on customerloyalty have no significant and positive effect. The effect of service quality on customer loyaltyhas a significant positive effect